Modern View on Information Services Provided by Service Centers of the Ministry of Internal Affairs of Ukraine - О. V. Dzhafarova; O. H. Kniaziuk (Bulletin of Kharkiv National University of Internal Affairs)
Procedures for the implementation of information services provided by service centers of the Ministry of Internal Affairs of Ukraine have been studied. The analysis of doctrinal provisions allowed us to conclude about the multiplicity of information services and differences in the procedure for their provision, which necessitated the classification of these procedures in order to identify their fundamental features, namely: depending on the subject of provision; according to the method of providing information; depending on the need for payment; depending on the availability of the information service procedure; according to the definition of the range of consumers; depending on the possibility of refusing to provide this type of administrative services; according to the content of the information service.